Non‐human primate models of Parkinson's disease: Decoding pathogenesis and advancing therapies - Sihui Zhang; Lin Yuan; Zihan Wu; Xuguang Du; Jacek Z. Kubiak; Feng Yue; Xuejing Yan; Gaolin Jiang; Yongye Huang (Brain-X, 2025)
Abstract Parkinson's disease (PD) is a neurodegenerative disorder in which the clinical manifestations include resting tremor, bradykinesia, akinesia, rigidity, and postural instability. The disease can be accompanied by non‐motor symptoms such as depression and insomnia. The leading factors in the initiation of this disease include genetic alteration, exposure to toxins, and age. However, the exact mechanisms underlying the pathogenesis of PD remain elusive. Animal models play a critical role in the research on the pathogenesis and treatment of PD. Non‐human primates share similar characteristics with humans, particularly in motor and cognitive abilities and the complexity of the neural structure. Non‐human primate models for PD can be roughly classified into spontaneous, neurotoxin‐based, and gene‐editing models. Although having several current limitations, non‐human primate models can play an increasingly important role in the research on PD, especially given the rapid development of novel methods in neuroscience.